2015
DOI: 10.1530/rep-15-0126
|View full text |Cite
|
Sign up to set email alerts
|

New insights into the function of Cullin 3 in trophoblast invasion and migration

Abstract: Cullin 3 (CUL3), a scaffold protein, assembles a large number of ubiquitin ligase complexes, similar to Skp1-Cullin 1-F-box protein complex. Several genetic models have shown that CUL3 is crucial for early embryonic development. Nevertheless, the role of CUL3 in human trophoblast function remains unclear. In this study, immunostaining revealed that CUL3 was strongly expressed in the villous cytotrophoblasts, the trophoblast column, and the invasive extravillous trophoblasts. Silencing CUL3 significantly inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 30 publications
0
23
0
Order By: Relevance
“…They have been confirmed participated in regulating cell’s proliferation [4042]. Some studies found that Cullin-3 and beta actin regulated cell migration [43, 44]. The relationship between these proteins and Talin-1 has not been researched..…”
Section: Discussionmentioning
confidence: 99%
“…They have been confirmed participated in regulating cell’s proliferation [4042]. Some studies found that Cullin-3 and beta actin regulated cell migration [43, 44]. The relationship between these proteins and Talin-1 has not been researched..…”
Section: Discussionmentioning
confidence: 99%
“…Trophoblast cell dysfunction can lead to pregnancy-related diseases such as intrauterine growth restriction, preeclampsia, eclampsia, spontaneous abortion, premature delivery, and choriocarcinoma [14].…”
Section: Discussionmentioning
confidence: 99%
“…The discovery that CUL3 controlled the abundance of TIAM1, the activity of RAC1 (the substrate of TIAM1) and the retinoic acid response suggested that CUL3 was implicated in cell differentiation, proliferation, apoptosis and other cellular processes. Recent research demonstrated an essential role for CUL3 in the invasion and migration of trophoblast cells . CUL3 might participate in bladder cancer aggressiveness by modifying the expression of cytoskeleton proteins .…”
Section: Discussionmentioning
confidence: 99%